Philippines 5000. (SEC in joint cooperation with Credit Information Bureau, Inc., 1995)
"Philippines 5000 is an annual publication of the Securities and Exchange Commission (SEC)." This shall serve as a primary vehicle for book local and international investors to identify potential investment needs and business opportunities in the country particularly in Mandaluyong.